Cosmic strings with junctions : dynamics and cosmological implications - Pourtsidou, Alkistis (2011)
Cosmic strings are linear concentrations of energy that may have been formed after cosmological phase transitions in the early universe. Cosmic superstrings are analogous objects arising in string theory, and in particular in models of brane inflation. The latter possess two particular features, which differentiate them from the ordinary cosmic strings: a reduced intercommuting probability, and the ability to form junctions. This thesis is concerned with the dynamics and cosmological implications of cosmic strings and superstrings with junctions. In Chapter1, we give a brief introduction to the standard Big Bang model and t he inflationary paradigm. W e also discuss cosmic string formation after the spontaneous breaking of an Abelian U (I) gauge symmetry in the early Universe. In Chapter 2, we present an overview of cosmic string dynamics using the Nambu-Goto method. We discuss the properties of individual cosmic string segments and loops, as well as network evolution in an expanding Universe. We also introduce cosmic superstrings, and review the Nambu-Goto approach to study the evolution of junctions and the kinematic constraints that govern their formation. We conclude with the study of junctions in an expanding spacetime and present an exact solution for a closed loop of three strings and two junctions in a de Sitter Universe. In Chapter3, we compare the two different approaches developed to study the dynamics of strings with junctions. We first extensively study the dynamics and stability of a cosmic string loop with junctions using the modified Nambu-Goto approach. Comparing our results with a field theory model that permits junctions we find very good agreement. The Nambu-Goto method is once again confirmed to be a good approximation for studying cosmic string configurations. In Chapter4, we review the observational signatures of cosmic strings. More specifically, we concentrate on their gravitational effects, discussing results and constraints from lensing, gravitational radiation, CMB and pulsar timing. We also present recent results of the case of cosmic (super)-strings with junctions. Chapter5 is concerned with the cosmological implications of cosmic superstring networks. W e first study the scaling patterns of such networks for different values of the string coupling g8, and different charges (p, q) on the strings. We then focus on their CMB signatures and derive upper bounds for the fundamental tension MuF using CMB and pulsar timing constraints. The difference between the scaling behaviour of the networks at high and low values of g, is imprinted as a movement of the position of the peak in the B –mode spectrum. Together with the constraints on GMuF from CMB and pulsar timing, this allows for the exciting possibility to constrain the value of the string coupling g8 using CMB data. We conclude in Chapter 6.